2018
DOI: 10.3126/jucms.v4i2.19082
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Dysfunction in Irritable Bowel Syndrome

Abstract: INTRODUCTION:Irritable bowel syndrome (IBS) is a common public health problem. The condition is characterized by a scarcity of biological markers; thus, diagnostic definitions and classifications have relied to a large extent on symptoms, gastrointestinal manifestations of patients. While thyroid disorder should be considered in the differential diagnosis of patients with IBS symptoms, it is not clear if thyroid disturbances amongst patients with IBS are high enough to warrant routine screening. This study was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…Moreover, there was no significant difference in thyroid function tests between the control and IBS groups. Against our results, Khadka et al showed that thyroid dysfunction was more prevalent in those associated with irritable bowel syndrome (19%) than in the overall population [ 17 ].…”
Section: Discussionsupporting
confidence: 49%
“…Moreover, there was no significant difference in thyroid function tests between the control and IBS groups. Against our results, Khadka et al showed that thyroid dysfunction was more prevalent in those associated with irritable bowel syndrome (19%) than in the overall population [ 17 ].…”
Section: Discussionsupporting
confidence: 49%
“…Sixty-ve percent of our patients were overweight/obese, which is higher compared to European studies (7)(8)(9). In addition, a Korean study showed that visceral adiposity was correlated with an increased risk of IBS and especially IBS-D, but no signi cant association was found between BMI and IBS (7).…”
Section: Discussioncontrasting
confidence: 48%
“…The effect of hypothyroidism, which was associated with an impairment of mainly physical but also mental quality of life (RE) and SF36 global score, was explained by hormonal interactions detailed in a study conducted in Nepal (9).…”
Section: Discussionmentioning
confidence: 99%
“…Sixty-ve percent of our patients were overweight/obese, which is higher compared to European studies (7)(8)(9). In addition, a…”
Section: Resultsmentioning
confidence: 50%